Inhibition of human colon carcinoma cell growth by ammonia: a non-cytotoxic process associated with polyamine synthesis reduction - Mouillé, Béatrice; Delpal, Serge; Mayeur, Camille; Blachier, François (Biochimica et biophysica acta, 2003)
Ammonia, produced by bacterial degradation of unabsorbed and endogenous nitrogenous compounds, is found to be present at millimolar concentrations in the colon lumen. From in vivo animal experiments, this metabolite has been shown to alter colonic epithelial cell morphology and to increase compensatory cell proliferation when present in excess. In this in vitro study, using the human colon adenocarcinoma HT-29 Glc −/+ cell line treated with increasing doses of NH 4Cl, we found that 20 mM NH 4Cl, a concentration close to that found in the large intestine lumen, was able to increase the volume of vacuolar lysosomes and to repress HT-29 Glc −/+ cell proliferation. This growth-inhibitory effect was not correlated with decrease of cell viability, with modification of cell differentiation and change of the cell distribution in the different cell cycle phases, thus indicating a proportional slowdown in all cell cycle phases. In contrast to what is found in healthy colonocytes, ammonia was not metabolized by HT-29 cells into carbamoyl-phosphate (carbamoyl-P) and citrulline, indicating that ammonia was likely acting on cells by itself. This agent was shown to markedly reduce cellular ornithine decarboxylase (ODC) activity resulting in a threefold decrease in the capacity of HT-29 cells to synthetize polyamines, these latter metabolites being strictly necessary for cell growth. The unexpected finding that ammonia is acting as an antimitotic agent against tumoral HT-29 colonic cells may be related to the inability of these cells to metabolize this compound.